A fogyasztók biotermékekkel kapcsolatos ismeretei Romániában - Pál, Zsuzsa; Pápay, Orsolya (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
In the last twenty years the organic movement has faced a great interest. Europe has the largest organic market; however the demand for organic foods is concentrated in Western Europe. The Central and Eastern European countries, like Romania, are becoming important cereal suppliers for the Western Europe. Despite the increasing of the home organic production, the Romanian consumer does not buy and eat organic food products. This paper investigates the barriers of the organic food choice. A study was delivered in Cluj Napoca city among the adult population. The aim of the study was describing the consumers’ buying behaviour in an organic food purchasing context. The questionnaire was structured into five sections: general food purchasing habits, the consumer’ knowledge regarding the organic foods, organic foods buying habits, reasons of the nonconsumption and identification questions. The accent is put on the evaluation of the consumers’ knowledge on this category of products. The main conclusion is despite the consumers consider them-selves consuming organic food, they do not are able even to identify or characterize them.